Fugitive Testimony : On the Visual Logic of Slave Narratives - Neary, Janet (Book collections on Project MUSE., 2017)
"Fugitive Testimony examines African American slave narratives in light of contemporary artists' use of the genre within their visual art at the end of the twentieth century. It identifies a sustained representational strategy employed by black cultural producers across time to challenge the racial presumptions that manifest as artistic constraints."--Provided by publisher.